Pengembangan Aplikasi Mobile POVSHOT untuk Penjualan Foto Online Menggunakan Flutter dan MySQL - Cahaya Citra Azzahro; Johan Krisbima Abi; Octavian Dava Putra; Agil Gilang Chandra Saputra; Fadlil Liwaul Hamdi; Ach. Fasihul Lisan (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The rapid advancement of information and communication technology has transformed and opened business perspectives and operations, particularly in UMKM the photography industry. As the demand for online photography services continues to rise, it is crucial for service providers to develop efficient information systems to manage photo sales effectively. The research titled "Development of the POVSHOT Mobile Application for Online Photo Sales Using Flutter and MySQL" aims to facilitate online photo sales through the implementation of Flutter technology and a MySQL database. The findings indicate that the "POVSHOT" application successfully integrates features such as photo uploading, payment management, and user administration within a user-friendly interface. This study suggests that the use of mobile applications can enhance security in the photo sales process and provide a better experience for users. The implications of this research highlight that photography service providers can leverage mobile technology to expand their market reach and improve customer satisfaction through a more integrated and responsive system.